Thermodynamic Simulation of Precipitation Phase Evolution in 2324 Aluminum Alloy by Jmat Pro - ZHAO Ming-ming; GUO Er-jun; FENG Yi-cheng; FU Jin-lai; WANG Li-ping; FU Yuan-ke (Journal of Harbin University of Science and Technology, 2021)
2324 aluminum alloy has excellent comprehensive performance, especially high damage tolerance performance As a structural material, it has been widely used in advanced large aircraft, and its heat treatment process is the key to ensure high comprehensive performance.This paper takes 2324 aluminum alloy for industrial use as the research object. The equilibrium phase composition, metastable phase, TTT/CCT curve and isothermal aging phase composition of 2324 aluminum alloy are simulated by JMatPro software, and the heat treatment process parameters are optimized. The results show that the phase composition of 2324 aluminum alloy at room temperature is 88.02% α(Al), 7.28% S(Al2CuMg), 2.45% Al6Mn, 1.35% Al2Cu, 0.63% E(AlCrMgMn) and 0.27% Mg2Si, among which S phase is the main strengthening phase.The metastable phase of the alloy is S′ phase, Q′ phase and η′ phase, among which S′ phase is the main strengthening phase during the aging process.The TTT curve calculation show that during the heat treatment, the tip temperatures of GP zone, η′, S′, η(MgZn2) and S phase increase successively, which are 170℃, 300℃, 350℃, 360℃ and 420℃ respectively, and the corresponding incubation times are 5.45s, 40.91s, 15.23s, 920.62s and 305.83s respectively The CCT curve calculation shows that the critical cooling rates of GP zone, η′, S′, η(MgZn2) and S phase without precipitation during heat treatment are 0.95℃/s, 1.72℃/s, 5.22℃/s, 0.16℃/s and 0.90℃/s respectively.When aging at 190℃, the precipitation amount of S′ phase is larger, and the complete aging time is shorter.When the aging time is 5~10h, the strengthening phase content is higher, and there is also a certain content for GP zone.Therefore, by the above results, the optimal heat treatment process can be obtained: the cooling rate of the cooling medium is greater than 5.22℃/s in the solid solution treatment, the solid solution transfer time of the sample is less than 5.45s, and the aging temperature and time are respectively set at 190℃ and 5~10h.